Promoter methylation status of the TIMP2 and ADAMTS4 genes and patellar tendinopathy. Issue 4 (April 2018) - El Khoury, Louis Y.; Rickaby, Rebecca; Samiric, Tom; Raleigh, Stuart M.
Abstract: Objectives: Patellar tendinopathy (PT) is a debilitating and prevalent condition that tends to affect those who are physically active or engaged in jumping sports. Although tendinopathies are known to have a genetic basis, the role of DNA methylation as an epigenetic factor and risk determinant for human PT has never been described. We sought to determine whether differences existed between the methylation profiles of both the TIMP2 and ADAMTS4 gene promoter sequences in a cohort of males having undergone surgery for patellar tendinopathy compared to controls. Design: Case-control epigenetic study using DNA from 10 males with PT and 10 males with healthy tendons. Methods: We used PCR and targeted pyrosequencing to interrogate the methylation profiles of CpG sites upstream of both the TIMP2 (4 sites) and ADAMTS4 (6 sites) genes. We compared methylation differences between the two groups using t-tests. Results: We report no significant (p > 0.05) methylation differences within the TIMP2 gene promoter between the PT group and controls across the 4 CpG sites investigated. In contrast, we detected a significant (p = 0.016) difference in the methylation status of 1 CpG site, approximately 3 kb upstream of the ADAMTS4 gene between the PT group and controls. Conclusions: To our knowledge, this is the first study to investigate how DNA methylation impacts on the risk of human tendinopathy. Our data indicate that the methylation status of the ADAMTS4 gene is altered in patellar tendinopathy and we speculate on how this change might modify the patellar tendon extra-cellular matrix environment.